Context-Aware Systems and Applications First International Conference, ICCASA 2012, Ho Chi Minh City, Vietnam, November 26-27, 2012, Revised Selected Papers - Vinh, Phan Cong.; Hung, Nguyen Manh.; Tung, Nguyen Thanh; Suzuki, Junichi; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2013)
This book constitutes the thoroughly refereed proceedings of the first International Conference on Context-Aware Systems and Applications, ICCASA 2012, held in Ho Chi Minh City, Vietnam, in November 2012. The 34 revised full papers presented were carefully selected and reviewed from over 100 submissions. The papers cover a wide spectrum of issues in the area of Context-Aware Systems (CAS). CAS are going to shape networked computing systems of the future
Activity-Based Entities Relationship in Monitoring Context Awareness -- Context-Aware User Preferences in Systems for Pervasive Computing and Social Networking -- Context-Aware Security Solutions for Cyber Physical Systems -- 3D Interaction Assistance in Virtual Reality: A Semantic Reasoning Engine for Context-Awareness -- An Energy-Efficient Ring Search Routing Protocol Using Energy -- A Formal Approach to Modeling and Verifying Resource-Bounded Context-Aware Agents -- Context-Aware Design of Semantic Web Services to Improve the Precision of Compositions -- Towards Context-Aware Recommendation for Personalized Mobile Travel Planning -- Concept of the Personal Devices Content Management Using Modular Architecture and Evaluation Based Design -- Object Detection and Tracking in Contourlet Domain -- User Preferences Elicitation and Exploitation in a Push-Delivery Mobile Recommender System -- Emotion Analysis of the Text Using Fuzzy Affect Typing over Emotions -- Compare Effective Fuzzy Associative Memories for Grey-Scale Image Recognition.
Keywords: Computer science; Information storage and retrieval systems; Artificial intelligence; Optical pattern recognition; Computer Science; Information Storage and Retrieval; Information Systems Applications (incl. Internet).; User Interfaces and Human Computer Interaction; Artificial Intelligence (incl. Robotics).; e-Commerce/e-business.; Pattern Recognition